Motivasi siswa SMP Negeri 13 kota serang dalam mengikuti ekstrakulikuler berbasis sastra di sekolah - Pertiwi, Ismiati; Rizal, Atika Ramadhan; Nabilla, Syifa Aulia; Damayanti, Lely; Wahyuni, Sasa Indri; Aditya, Luthfi (Universitas Lampung, 2024)
The purpose of this study is to know te various motivation of SMP Negeri 13 Kota Serang students in nonliterary extracurricular activities. This study is a explanatory quantitative research methods. The data collection technique used in this research is form of a questionnaire. This research was taken from students at SMP Negeri 13 Serang using a simple random sampling. The results of the research showed that the competition and competency indicators reached a percentage of 37% with the descriptor